ADVANCES IN MINIMALLY INVASIVE SURGERY FOR THE MANAGEMENT OF UPPER URINARY TRACT ANOMALIES IN CHILDREN - Julia Załęcka; Katarzyna Moliszewska; Paweł Kukiełka; Joanna Kośka; Gabriela Łocik; Julia Mazurek; Alicja Nowik; Kacper Dywan; Martyna Musiorska; Michał Błaszkiewicz; Julia Żak (International Journal of Innovative Technologies in Social Science, 2025)
Background. Minimally invasive surgery (MIS) has significantly evolved in pediatric urology, offering alternatives to traditional open techniques by reducing postoperative morbidity, improving cosmetic outcomes, and accelerating recovery. Technological advancements, especially the miniaturization of instruments and the introduction of robotic systems, have expanded the indications and efficacy of MIS for upper urinary tract anomalies in children.Aim. To review the current applications, outcomes, and future directions of minimally invasive techniques in the treatment of upper urinary tract anomalies in the pediatric population.Material and Methods. This narrative review summarizes data from published literature regarding laparoscopic and robot-assisted procedures in pediatric urology. It analyzes indications, technical considerations, benefits, limitations, and comparative outcomes of MIS versus open surgery, focusing on procedures such as pyeloplasty, nephrectomy, ureteroureterostomy, and ureterocalicostomy.Results. MIS approaches demonstrated reduced hospital stays, less blood loss, lower opioid use, and improved cosmetic results with comparable complication rates to open surgery. Robot-assisted procedures, particularly pyeloplasty, showed promising safety and efficacy—even in infants—and allowed for outpatient, stent-free interventions. Challenges remain in cost, equipment scaling for pediatric patients, and training requirements.Conclusions. MIS, including robotic-assisted surgery, is becoming the gold standard for many upper urinary tract interventions in children. Continued technological advancement and surgical expertise are expected to further enhance outcomes, expand indications, and improve the quality of care in pediatric urology.